2020
DOI: 10.3390/s20185089
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Capture and Raman Analysis of Circulating Tumor Cells by Nano-Undulated AgNPs-rGO Composite SERS Substrates

Abstract: The analysis of circulating tumor cells (CTCs) in the peripheral blood of cancer patients is critical in clinical research for further investigation of tumor progression and metastasis. In this study, we present a novel surface-enhanced Raman scattering (SERS) substrate for the efficient capture and characterization of cancer cells using silver nanoparticles-reduced graphene oxide (AgNPs-rGO) composites. A pulsed laser reduction of silver nanowire-graphene oxide (AgNW-GO) mixture films induces hot-spot formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 63 publications
(92 reference statements)
0
6
0
Order By: Relevance
“…In Figure S7b, the two most intense peaks of rGO were detected at 1345.6 cm −1 as the D band and the G band at 1585.5 cm −1 . 40 When Raman spectra of CN-rGO and BPQDs/CN-rGO were examined, it was observed that the intensities of the D and G bands of rGO remained unchanged. In addition, the blue shift of these rGO peaks in the CN-rGO and BPQDs/ CN-rGO heterojunctions indicates that there are internal interactions between the components.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Figure S7b, the two most intense peaks of rGO were detected at 1345.6 cm −1 as the D band and the G band at 1585.5 cm −1 . 40 When Raman spectra of CN-rGO and BPQDs/CN-rGO were examined, it was observed that the intensities of the D and G bands of rGO remained unchanged. In addition, the blue shift of these rGO peaks in the CN-rGO and BPQDs/ CN-rGO heterojunctions indicates that there are internal interactions between the components.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“… However, these peaks screened in the range of 350–500 cm –1 were not observed due to the low content of BPQDs in the ternary heterojunction. In Figure S7b, the two most intense peaks of rGO were detected at 1345.6 cm –1 as the D band and the G band at 1585.5 cm –1 . When Raman spectra of CN-rGO and BPQDs/CN-rGO were examined, it was observed that the intensities of the D and G bands of rGO remained unchanged.…”
Section: Resultsmentioning
confidence: 99%
“…The Disordered band associated with large number of defects can provide conducive surface reactions alongwith active adsorption sites for gas sensing. 72 The intensity ratio of D, G bands is related to the defects density and graphitization. The I D /I G value FTIR.-To ascertain functional group presence and identification of molecular absorption, reduction of rGO and composite formation, Fourier Transform IR spectroscopy (FTIR) measurements presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These few‐weeks old substrates deposited with 50 nm Ag show decent and significantly enhanced signal for the corresponding molarities compared to normal Raman spectra of the same molecules. R6G and CV are commonly used dye molecules [ 36 ] whereas NH 4 NO 3 is used as fertilizer and explosive material which bears significance for its detection. The observed Raman bands in Figure 8a,c are partially common with BCB spectra shown in above figures, for the wavenumbers around 1200, 1400, and 1600 cm −1 whereas in NH 4 NO 3 characteristic peak is found at 1045 cm −1 denoting the N−O symmetric stretching.…”
Section: Resultsmentioning
confidence: 99%